2020
DOI: 10.1038/s41598-020-72701-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV-1 genotype on baseline CD4+ cell count and mortality before and after antiretroviral therapy

Abstract: To assess whether human immunodeficiency virus type 1 (HIV-1) genotype influences baseline CD4+ T lymphocyte (CD4+) cell count and mortality of patients. The study was conducted from 2014 to 2019 in Guangxi, China, and included 2845 newly diagnosed HIV patients. We used a median regression model to compare CD4+ cell counts in patients newly diagnosed with different HIV-1 genotypes, and a Cox regression model to analyze the associations between HIV-1 genotypes and mortality before and after antiretroviral treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…We have previously shown that CRF07_BC has a lower TDR prevalence than subtype B and CRF01_AE (1.5% vs. 4.8% vs. 5.6%) respectively 27 , 28 . Ge et al 29 and Cao et al 30 have demonstrated that CRF07_BC is associated with better immune recovery in Chinese patients undergoing antiretroviral treatment (ART) compared to that of patients infected with CRF01_AE. Taken together, these results support the hypothesis that CRF07_BC is less pathogenic than subtype B.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that CRF07_BC has a lower TDR prevalence than subtype B and CRF01_AE (1.5% vs. 4.8% vs. 5.6%) respectively 27 , 28 . Ge et al 29 and Cao et al 30 have demonstrated that CRF07_BC is associated with better immune recovery in Chinese patients undergoing antiretroviral treatment (ART) compared to that of patients infected with CRF01_AE. Taken together, these results support the hypothesis that CRF07_BC is less pathogenic than subtype B.…”
Section: Discussionmentioning
confidence: 99%
“… 26 A previous study conducted in Guangxi between 2014 and 2019 showed that patients in different HIV-1 subtype groups exhibited inconsistent baseline CD4 before ART but similar mortality after ART. 10 This study included the surveillance data between 2008 and 2020 and revealed that patients in different HIV-1 subtype groups had not only inconsistent baseline CD4 but also inconsistent subsequent clinical outcomes during ART. We found that the period of the first 12 months of ART initiation was critical for long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to relatively limited clinical data, a previous study in Guangxi between 2014 and 2019 provided insufficient evidence to validate this hypothesis. 10 In this study, we integrated 2 large databases of province-wide surveillance in China to compare the disparate impacts of HIV-1 subtypes on immunologic responses, virologic responses, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that people who are resistant to HIV have a deletion mutation in their CCR5 receptor gene, that results in a 32-base pair loss. In these cases, the normal CCR5 receptor protein cannot be encoded and so macrophages and dendritic cells lacking the CCR5 cannot be infected by the virus and individuals are resistant to AIDS [ 84 ]. Since the outbreak of the novel coronavirus, the mechanism of the invasion of human cells by COVID-19 has become clear.…”
Section: Association Between Membrane Proteins and Diseasementioning
confidence: 99%